2022
DOI: 10.1302/0301-620x.104b1.bjj-2021-0848.r2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of image-guided biopsy in patients with suspected infectious spondylodiscitis

Abstract: Aims The aims of this study were to determine the diagnostic yield of image-guided biopsy in providing a final diagnosis in patients with suspected infectious spondylodiscitis, to report the diagnostic accuracy of various microbiological tests and histological examinations in these patients, and to report the epidemiology of infectious spondylodiscitis from a country where tuberculosis (TB) is endemic, including the incidence of drug-resistant TB. Methods A total of 284 patients with clinically and radiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The average age in this study was 34 years, which was similar to the average age of presentation in other studies 31-35 years [3,4,11]. But compared to Epivatianous A. was 46.3 years [12]. So, the mean age for included patients was close for peoples in other regions.…”
Section: Age Distributionsupporting
confidence: 86%
“…The average age in this study was 34 years, which was similar to the average age of presentation in other studies 31-35 years [3,4,11]. But compared to Epivatianous A. was 46.3 years [12]. So, the mean age for included patients was close for peoples in other regions.…”
Section: Age Distributionsupporting
confidence: 86%
“…In recent years, the proportion of non-TB infections in patients with suspected spinal TB has increased gradually ( Tsantes et al, 2020 ). Although non-TB spinal infection and spinal TB have similar clinical symptoms and imaging findings, their treatment is contradictory ( Kafle et al, 2022 ). Thus, their differential diagnosis is required.…”
Section: Introductionmentioning
confidence: 99%
“…Tuberculous vertebral infection is evoked when granuloma or caseous necrosis with chronic inflammation is noted, whereas it is considered as definitive when acid-fast bacillus bacteria is positive [ 99 ]. Many studies have shown the superiority of cytopathology over microbiological investigations in establishing the diagnostic of PSI [ 100 ], since it was demonstrated that histology could provide the diagnostic even when no specific infectious agent was isolated [ [63] , [80] , [99] , [100] , [101] ]. Two papers reported of a sensitivity ranging between 81% and 91%, and a specificity of 100% for histologic examinations [ [100] , [101] ].…”
Section: Histopathological Assessmentmentioning
confidence: 99%